The real fairy storybook - Adams, Georgie; Gardner, Sally (London : Orion Books : Dolphin, 1999)
Blossom, the Royal Dressmaker, and her assistants tell their favorite stories as they work late into the night to sew the last pearls on to the Fairy Queen's dress.
4.7
3-6.
3-6
Keywords: Fairy tales; Sewing -- Fiction; Fairy tales; Sewing -- Fiction